CHANGES IN EJACULATE INDICATORS AFTER USING MICROSURGICAL TECHNIQUE IN THE TREATMENT OF MEN WITH VARICOCELE IN INFERTILITY - Khusanov S. M.; Akhmadaliev T. G.; Abdullaev A. A.; Bakhromov U. F. (Modern American Journals, 2025)
Varicocele is one of the frequently identified and corrected causes of male subfertility. However, varicocele correction results in improved sperm quality only in 60 – 70% of subfertile men. At the same time, it is not completely clear which semen parameters improve to a greater extent, and what is the proportion of patients with an improvement in parameters to normozoospermia.
Keywords: Semen; semen analysis; infertility; varicocele; varicocelectomy; asthenozoospermia; oligoasthenozoospermia.